Validation of the Fear of Pelvic Examination Scale (F-PEXS) – measuring students' fear of performing a pelvic examination. (March 2015) - Siwe, Karin; Wijma, Klaas
Abstract: Introduction : Medical students of both genders often show signs of fear before they perform their first pelvic examination. This situation puts a novice in a special setting of intimacy never experienced before and where different emotions may emerge. A specially designed questionnaire, the Fear of Pelvic Examination Scale (F-PEXS) has been developed to assess fear in this context. The aim of this paper is to describe the validation of the F-PEXS. Methods : Undergraduate medical students ( N  = 100) answered the F-PEXS one week before, prior to and after a learning session with professional patients to assess levels of anxiety towards performing the pelvic exam. The validity of the scale was examined using item analysis, reliability assessments and analysis of the construct validity in comparing the F-PEXS with the Spielberger State and Trait Anxiety Inventory and Beck's Anxiety Inventory. Results : The F-PEXS has very good reliability (Cronbach's alpha 0.96) and good construct validity. The mean score on the F-PEXS did not differ between gender either before or after the learning session. Conclusions : The F-PEXS can be used to assess students' fear of performing the pelvic examination, to evaluate new strategies for learning the pelvic exam and to evaluate the outcome of such interventions.